Trace quantification of 1‐triacontanol in beagle plasma by GC‐MS/MS and its application to a pharmacokinetic study. (21st October 2014) - Wang, Chunfeng; Fan, Ali; Zhu, Xiaojie; Lu, Yang; Deng, Shuhua; Gao, Wenchao; Zhang, Wei; Liu, Qi; Chen, Xijing
Abstract 1‐Triacontanol (TA), a member of long chain fatty alcohol, has recently been received great attention owing to its antitumor activity. In this study, an accurate, sensitive and selective gas chromatography–tandem mass spectrometry method was developed and validated for the quantification of TA in beagle plasma using 1‐octacosanal as the internal standard (IS) for the first time. With temperature programming, chromatographic separation was carried out on an HP‐5MS column, using helium as carrier gas and argon as collision gas, both at a flow rate of 1 mL/min. TA was analyzed using positive ion electrospray ionization in multiple‐reaction monitoring mode, with the precursor to product ion transitions of m/z 495.6 → 97.0 and m/z 467.5 → 97.0 for TA and the IS, respectively. The lower limit of quantitation, linearity, intra‐ and interday precision, accuracy, stability, extraction recovery and matrix effect of TA were within the acceptable limits. The validated method was successfully applied to a pharmacokinetic study of TA in beagles. Copyright © 2014 John Wiley & Sons, Ltd.